Digital collaborative writing technique using Padlet in essay writing classroom - Devi, Anit Pranita; Puspitasari, Rianny (ELT in Focus, 2023)
This research explores the utilization of Padlet as a collaborative writing platform in enhancing students' argumentative essay writing skills. Employing a case study by means of observation, document analysis, and interviews, the study examines how Padlet is employed on collaborative essay writing classroom and how it facilitates students’ writing skills in argumentative essay writing process. The research findings reveal that while Padlet effectively fosters collaborative interactions among students, enabling them to engage in constructive feedback provision and substantive discussions, its underutilization remains noticeable. The platform's inability to facilitate targeted feedback due to the absence of specific text highlighting and commenting features emerged as a critical limitation hindering comprehensive feedback provision. In spite of these limitations, Padlet significantly improved various dimensions of students' writing skills. The collaborative environment nurtured by Padlet enabled peer feedback exchange, leading to enhancements in grammar, vocabulary, coherence, and overall essay quality. However, students' restricted exploration of Padlet's features underscores the gap between its potential and actual utilization within the classroom. To advance this research, future studies should focus on addressing Padlet's functional limitations by advocating for feature enhancements facilitating targeted feedback.